Effect of Transactional Analysis on the Psychosocial Challenges of Secondary School Adolescents - Ayodeji, Badejo; Bola, Lamidi Salimot; Benjamin, Etobro A. (Universitas Negeri Semarang, 2022)
This study examined the effect of Transactional Analysis on the psychosocial challenges of adolescence. Two research hypotheses were made to guide the study. The sample consisted of seventy (106) senior secondary school students. A-40 item self-developed questionnaire was designed for data collection. The study adopted a quasi-experimental control group design. Analysis of data was achieved using Analysis of Co-variance (ANCOVA) at 0.05 level of significance. The result of the findings showed that there was a significant effect of Transactional Analysis on the psychosocial challenges of adolescents F(1, 104) = 275.882, p 0.05 and that family dispute did not have significant effect on secondary school adolescents’ psychosocial challenges, F ( 2, 104) = 0.414, p 0.05. The treatment, Transactional Analysis applied in this study was effective in the reduction of psychosocial challenges among secondary school adolescents. Counsellors should be proactive in identifying adolescents with psychosocial problems and assist them through the use of Transactional Analysis. It is recommended that counsellors, educational administrators, and policymakers should always make use of this counselling therapy, when handling adolescents’ challenges.